2011
DOI: 10.1002/ejlt.201100088
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of the polymorphic forms and liquid state of cocoa butter

Abstract: Raman spectroscopy was used to characterize the polymorphs and liquid state of cocoa butter, with emphasis placed on the evolution of the ester carbonyl stretching region (1800–1700 cm−1), along with complementary analysis and comparison of the Raman‐active CC (1200–1000 cm−1), CC (1660 cm−1), CH (3000–2700 cm−1) and CH2 (1500–1250 cm−1) vibrational modes. Unique Raman signatures were obtained for all cocoa butter polymorphs, with their identity confirmed using DSC and XRD. The ester carbonyl region permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 38 publications
5
62
0
3
Order By: Relevance
“…This suggests that conformational differences exist between the polymorphs of SHs and Si‐SHs around the carbonyl bond, which is resolvable in Raman spectra. Similar observations were reported in the case of cocoa butter TAGs , StOSt (by conventional IR) and tristearin . However, Sprunt et al reported two bands for the β form of StOSt TAG.…”
Section: Resultssupporting
confidence: 78%
“…This suggests that conformational differences exist between the polymorphs of SHs and Si‐SHs around the carbonyl bond, which is resolvable in Raman spectra. Similar observations were reported in the case of cocoa butter TAGs , StOSt (by conventional IR) and tristearin . However, Sprunt et al reported two bands for the β form of StOSt TAG.…”
Section: Resultssupporting
confidence: 78%
“…These results indicated that PHEMA brushes were successfully grafted onto the PVC membrane surface. For the PVC‐g‐PHEMA‐g‐PBVIm‐Br membrane (M2), an obvious absorption band appeared at around 1163 cm −1 , which was correlated with C─H stretching in the imidazole ring. Meanwhile, the adsorption peak at 1563 cm −1 was attributed to the stretching vibration adsorption peak of ─C═N in the imidazole ring.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Raman spectroscopy was used to characterize the different polymorphs of CB. Unique signatures were detected for all CB polymorphs . With X‐ray diffraction and Raman Spectroscopy, it is thus possible to identify the β VI polymorph in CB, which is often linked with the presence of fat bloom.…”
Section: Relationships Between Chocolate Microstructure and Polymorphmentioning
confidence: 98%